Studi Kasus Kebocoran Data SIM Card oleh Bjorka: Dampaknya terhadap Kepercayaan Publik terhadap Keamanan Digital di Indonesia - Syifa Nurul Sabila; Wira Atman (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study aims to critically analyze the impact of the SIM card data leak by an anonymous actor named Bjorka on the level of public trust in digital security in Indonesia which first appeared in mid-2022, precisely in August 2022. In addition, it evaluates the extent to which the national legal system is able to provide protection for digital service users and examines the social, moral, and ethical responses of society in addressing the incident. This case demonstrates that data breaches are not merely technical issues but also shake the legitimacy of the state in safeguarding citizens’ privacy rights, while revealing gaps in regulatory systems and data governance. This research employs a qualitative approach with a descriptive method. Data were collected through literature reviews of scholarly articles, academic journals, policy reports, and relevant opinion pieces. The findings indicate that Bjorka’s data breach incident triggered a crisis of public trust in government institutions and digital service providers. The public responded with fear, anger, and disappointment, mainly due to the lack of transparency and accountability from the responsible parties. Moreover, the implementation of Law No. 27 of 2022 on Personal Data Protection is considered ineffective, both in terms of law enforcement and the readiness of technical and institutional infrastructure.